IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF "RODA LITERASI" DALAM MENINGKATKAN KETERAMPILAN LITERASI SISWA SDN 48 AMPENAN - Fitri Indah Rahmawati; Elly Nurfitriani; Maysa Ayu; Hidayatullah; Irma Auli; Syafruddin Muhdar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the implementation of the interactive learning media Roda Literasi in improving students’ literacy skills at SDN 48 Ampenan. This study employed a descriptive qualitative method involving 24 fifth-grade students as the research subjects. Data were collected through observation and documentation techniques. The data were analyzed using the Miles and Huberman model, including data collection, data reduction, data display, and conclusion drawing. The results showed that the implementation of Roda Literasi through reading, storytelling, speaking, and playing activities was able to increase students’ participation in the learning process. Students became more active, confident in reading and speaking in front of the class, and more enthusiastic during learning activities. In addition, the use of interactive media created a more enjoyable and engaging learning atmosphere. Therefore, Roda Literasi can be used as an innovative learning medium to improve elementary school students’ literacy skills.